Detection and Characterization of Carbapenemases in Enterobacterales With a New Rapid and Simplified Carbapenemase Detection Method Called rsCDM - Liao, Quanfeng; Yuan, Yu; Zhang, Weili; Deng, Jin; Wu, Siying; Liu, Ya; Xiao, Yuling; Kang, Mei (Frontiers in Microbiology, 2022)
Objective: This study aimed to develop a new method for rapid and simplified detection and characterization of carbapenemase with β-lactamase inhibitors. Method: A panel of 161 CRE strains with KPC (78), NDM (57), IMP (9), VIM (3), OXA-181 (1), porin changes in combination with an extended-spectrum β-lactamase (ESBL) (3) or AmpC hyper-production (4) and 23 non-carbapenemase-producing isolates were used to evaluate the performance of rsCDM. Carbapenemase class was determined with specific inhibitors at 4 h, 6 h and 18 h, and the difference between imipenem (IPM) and meropenem (MPM) disks was simultaneously compared. Results: The sensitivity of rsCDM using IPM was 99.4% at the three time points, with a specificity of 100%, independent of the culture duration. Similar to IPM, MPM disk also showed high sensitivity (99.4%) and specificity (100%) at 6 h. Based on a decision algorithm, the characterization number of IPM and MPM in KPC isolates was 78 vs. 77, metallo-β-lactamases (MBLs) was 69 vs. 68, KPC and NDM was 6 vs. 6 at 4 h, respectively. After 6 h, the category number changed insignificantly except for isolates with combined AmpC overproduction and porin changes, showing an increase in IPM (4) and MPM (1), and there was no difference in the results between 6 h and 18 h for the two tablets. Three ESBLs and one OXA-181 strains could not be detected by rsCDM. Conclusion: rsCDM accurately discriminated carbapenemase within 4 h and could differentiate AmpC in conjunction with porin changes strains. Hence, rsCDM represents a rapid, simple, easy readout and accurate tool that can be used without any specialized equipment.